Factors Affecting the Decontamination Process in Hospitals in Saudi Arabia - Felemban EM; Youssef HAM; Al Thobaity A (Dove Medical Press, 2021)
Ebaa M Felemban, Hanan AM Youssef, Abdulellah Al Thobaity Nursing Department, Applied Medical Sciences, Taif University, Taif, Saudi ArabiaCorrespondence: Abdulellah Al ThobaityNursing Department, Applied Medical Sciences, Taif University, Taif, Saudi ArabiaEmail a.thobaity@tu.edu.saIntroduction: Hospitals face various types of disasters that require either decontamination or disinfection interventions. These contaminants can be chemical, biological, radioactive, or infectious, such as COVID-19. Further, there are few studies in the literature on factors affecting decontamination in hospitals in Saudi Arabia.Methods: Approximately 157 healthcare providers (doctors, nurses, and other specialists) participated in this study. Principle component analysis was used to explore three factors in Saudi Arabia that affect the ability of healthcare providers to decontaminate appropriately.Results: Three factors were extracted: (1) having adequate skills to perform decontamination, (2) being adequately prepared for decontamination before a disaster occurs, and (3) organizational barriers to decontamination. There was a positive correlation between the skills and preparedness and a negative correlation between barriers and both skills and preparedness.Discussion: It is essential to prepare for decontamination during disasters more effectively and to ensure that all healthcare providers have the requisite skills. Moreover, barriers to decontamination must be investigated thoroughly to improve implementation.Keywords: risk, disaster, COVID-19, healthcare providers